Conductive CoOOH as Carbon‐Free Sulfur Immobilizer to Fabricate Sulfur‐Based Composite for Lithium–Sulfur Battery - Wang, Zhen‐Yu; Wang, Lu; Liu, Sheng; Li, Guo‐Ran; Gao, Xue‐Ping (Advanced functional materials, 2019)
Lithium–sulfur battery is recognized as one of the most promising energy storage devices, while the application and commercialization are severely hindered by both the practical gravimetric and volumetric energy densities due to the low sulfur content and tap density with lightweight and nonpolar porous carbon materials as sulfur host. Herein, for the first time, conductive CoOOH sheets are introduced as carbon‐free sulfur immobilizer to fabricate sulfur‐based composite as cathode for lithium–sulfur battery. CoOOH sheet is not only a good sulfur‐loading matrix with high electron conductivity, but also exhibits outstanding electrocatalytic activity for the conversion of soluble lithium polysulfide. With an ultrahigh sulfur content of 91.8 wt% and a tap density of 1.26 g cm−3, the sulfur/CoOOH composite delivers high gravimetric capacity and volumetric capacity of 1199.4 mAh g−1‐composite and 1511.3 mAh cm−3 at 0.1C rate, respectively. Meanwhile, the sulfur‐based composite presents satisfactory cycle stability with a slow capacity decay rate of 0.09% per cycle within 500 cycles at 1C rate, thanks to the strong interaction between CoOOH and soluble polysulfides. This work provides a new strategy to realize the combination of gravimetric energy density, volumetric energy density, and good electrochemical performance of lithium–sulfur battery. Conductive cobalt oxyhydroxide (CoOOH) sheets are prepared as the carbon‐free immobilizer for Li–S batteries for the first time. The S/CoOOH composite exhibits outstanding electrochemical performance resulting from the remarkable conductive framework and electrocatalytic activity contributed by the CoOOH sheets. Moreover, such composite delivers high gravimetric and volumetric energy densities, owing to the high sulfur content and tap density.